Effect of Porous Rectangular Type Baffle Block Angle on Hydraulic Jump Downstream of Spillway - Djunur, Lutfi Hair; Pallu, Muhammad S.; Karamma, Riswal; Bakri, Bambang (Civil Engineering Journal, 2024)
The elevation of the water surface upstream of the spillway structure increases significantly due to damming, leading to a rapid, supercritical flow downstream. This flow transitions from supercritical to subcritical, resulting in hydraulic jumps (Lj). The placement of a porous rectangular baffle block in the chute acts as an energy dissipator within the channel. This study aimed to investigate the effect of the angle of the porous rectangular baffle block on energy dissipation and hydraulic jumps downstream of the spillway structure. The experiment utilized a two-dimensional (2D) approach to evaluate energy dissipation and hydraulic jumps under various placements of the porous rectangular baffle block in the chute. The results indicated that the water level above the weir (hd) increased, along with turbulence downstream, while energy loss decreased. However, the efficiency of energy dissipation improved as variations in the water level above the weir decreased. A baffle block with an angle (α) of 60° was found to be the most effective in dissipating flow energy and shortening hydraulic jumps. Additionally, an empirical equation was developed for the hydraulic jump length as a function of the downstream Froude number (Fr): Lj=yt (k α hd(Fr-1)^4). The porous rectangular baffle block proved advantageous as it gradually dissipates flow velocity through its pore openings, preventing flow momentum reversal. Doi: 10.28991/CEJ-2024-010-10-04 Full Text: PDF